Making Refugees Work? Individualized Work Strategies in the Swedish Refugee Settlement Program - Wikström, Eva; Ahnlund, Petra (Nordic Journal of Working Life Studies, 2018)
In Sweden and elsewhere, work strategies have gained greater significance in social policy, and now also in settlement programs for refugees. This article addresses the level of practice of the refugee settlement program in Sweden, which previously emphasized ‘support’ and ‘social responsibility’, but now emphasizes ‘activation’ and ‘individual responsibility’. Through an analysis of interviews and individual action plans, we investigate how activation is put into practice in the work activities of refugee settlement and how employment officials and refugees articulate and experience the role that activation plays in refugees’ integration processes. The conclusion drawn is that activation is a central feature, but it involves conditionalizing elements that are used as the means to emphasize ‘work’ as the route to integration and to keep the ‘less employable’ refugees activated. The activation techniques applied require refugees to demonstrate that they are taking responsibility for their integration process and for increasing their employability.